ANALISIS DISTRIBUSI TEMPERATUR PERMUKAAN TANAH DI WILAYAH POTENSI PANAS BUMI DI SEKITAR SESAR PALU KORO MENGGUNAKAN TEKNIK PENGINDERAAN JAUH - Gregorius Siga; Cyrke Bujung; Jeilen Gabriela Nusa (Jurnal FisTa : Fisika dan Terapannya, 2021)
As one of the countries in the tropical region, Indonesia is blessed with various energy resources, one of which is geothermal energy. The existence of geothermal sources on the surface is reflected in the appearance of manifestations to the earth's surface, namely hot springs, fumaroles, etc. This study described the distribution of soil surface temperature to determine the surface temperature and the direction of the surface temperature opening around the Palu Koro Fault, Central Sulawesi. This study used remote sensing methods with thermal infrared channels recorded in 2015, 2017, 2018, 2019, and 2020. The results showed that the ground surface temperature in the geothermal potential area ranges from 31,5501°C - 38,8913°C, and the direction of the temperature opening is in the northwest to the southwest to the Southeast and is getting closer to the Palu Koro Fault.